TEORI SOSIAL DALAM PERSPEKTIF TEORI KRITIS MAX HORKHEIMER - Tjahyadi, Sindung (Jurnal Filsafat "WISDOM", 2007)
In this work, â€œHorkheimerâ€™s critical theoryâ€ is critically discussed in its relation with the presence of â€œprestigiousâ€ fact achieved by positivistic sciences. However, positivistic sciences have many contributions in providing the new dimensions for human life. In the case of Horkheimerâ€™s critical theory, it is clear that Horkheimer does not appreciate enough the positive-capitalistic approach. Even though, the antagonistic relation between â€œselfâ€ and â€œnatureâ€ in Horkheimerâ€™s point of view must be investigated. For social scientists that has social theory orientations and rigorous and applicative methodology, Horkheimerâ€™s critical theory is viewed as uncompleted social theory because he never provides a comprehensive method for social analyses. Even social theory properly leaves its function in â€œportrayingâ€ and analyzing community, Horkheimer reminds that there is a more important function of social theory called as â€œemancipatory-awarenessâ€. If human beings do not believe in optimism to pick up the better situation or to realize their â€œutopiaâ€, actually they have failed to sense their self-existence.